2021
DOI: 10.1021/acs.jpcb.1c03541
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of N6-Methyladenosine by the YTHDC1 YTH Domain Studied by Molecular Dynamics and NMR Spectroscopy: The Role of Hydration

Abstract: The YTH domain of YTHDC1 belongs to a class of protein "readers", recognizing the N6methyladenosine (m 6 A) chemical modification in mRNA. Static ensemble-averaged structures revealed details of N6-methyl recognition via a conserved aromatic cage. Here, we performed molecular dynamics (MD) simulations along with nuclear magnetic resonance (NMR) and isothermal titration calorimetry (ITC) to examine how dynamics and solvent interactions contribute to the m 6 A recognition and negative selectivity towards unmethy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…As expected the binding enthalpy with the hairpin RNA is slightly reduced compared to the single-stranded m 6 A RNA due to the local unfolding of the closing base pair. Interestingly, recognition of m 6 A in the context of both the single-stranded or the hairpin RNA ligand by the YTH domain shows slightly unfavorable binding entropy (consistent with previous reports), although the release of solvent molecules from the pocket of the protein that accommodates the N 6 methyl is expected to show favorable entropic contributions for binding ( 60 , 61 ).…”
Section: Discussionsupporting
confidence: 88%
“…As expected the binding enthalpy with the hairpin RNA is slightly reduced compared to the single-stranded m 6 A RNA due to the local unfolding of the closing base pair. Interestingly, recognition of m 6 A in the context of both the single-stranded or the hairpin RNA ligand by the YTH domain shows slightly unfavorable binding entropy (consistent with previous reports), although the release of solvent molecules from the pocket of the protein that accommodates the N 6 methyl is expected to show favorable entropic contributions for binding ( 60 , 61 ).…”
Section: Discussionsupporting
confidence: 88%
“…Others have shown that ignoring the size-dependent artifact can still give results that give a good correlation with the experimental data. 47 Similarly, there are studies that have shown that the Rocklin correction has very little effect on the RBFE calculations. 48 This is likely best explained by the fact that the Rocklin correction mainly corrects for the long-range effects of the electrostatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…So far, this has been only sparsely noted in the literature. (55)(56)(57)(58) The problem is now defined and documented in this work, by comparing the performance of the ff12SB, ff14SB, and ff19SB ffs for the isolated HuR RRM3 protein.…”
Section: System Building and Simulation Protocolmentioning
confidence: 99%